REPRESENTASI NILAI – NILAI PENDIDIKAN KARAKTER DALAM NOVEL AYAH KARYA ANDREA HIRATA - Wadiah, Nur; Asri, Yasnur; Hayati, Yenni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT This study aimed to describe the educational values of character in Andrea Hirata’s novel entitled Ayah. The research is a qualitative descriptive method. The approach taken in this study is a mimetic approach.This research data is in the form of words, phrases, sentences and the discourse displaying events and characters that indicate the educational values of character in Andrea Hirata’s Ayah novel including: (1) religious, (2) honest, (3) creative, (4) independent, (5) pacifist, (6) worker, (7) curious, (8) friendly, (9) who likes reading, (10) nationalist, and (11) patriotic. The techniques of collecting research data here are to read and understand, decide the main character and supporting character, inventory, interpret, and conclude.Kata kunci: nilai, pendidikan, karakter, implikasi